Contract, Culture, and Citizenship : Transformative Liberalism from Hobbes to Rawls - Button, Mark E. (Book collections on Project MUSE., 2008)
"Explores the concept of the social contract and how it shapes citizenship. Argues that the modern social contract is an account of the ethical and cultural conditions upon which modern citizenship depends"--Provided by publisher.